Ablation index-guided ablation with milder targets for atrial fibrillation: Comparison between high power and low power ablation - Liu, Zheng; Liu, Li-feng; Liu, Xiao-qin; Liu, Jiapeng; Wang, Yu-xin; Liu, Ye; Liu, Xing-peng; Yang, Xin-chun; Chen, Mu-lei (Frontiers in Cardiovascular Medicine, 2022)
Background High power-ablation index (HP-AI)-guided ablation for atrial fibrillation (AF) targeting high AIs has been implemented in European countries. However, milder AI targets are widely used in Asia. The safety and efficacy of HP-AI-guided ablation compared with those of low-power AI-guided ablation in a milder AI-targeting setting are unknown. The goal of this study was to explore the efficacy and safety of HP-AI-guided ablation in a milder AI-targeting setting. Methods Patients who underwent pulmonary vein isolation (PVI) for AI-guided atrial fibrillation ablation in our center were enrolled and divided into 2 groups according to the ablation power used. In the HP-AI group, the ablation power was over 45 W, while the low power-AI group was ablated with <35 W power. The targeted AIs were 450–500 in the anterior wall and 350–400 in the posterior wall. The efficacy outcome was expressed as the single-procedure atrial arrhythmia-free survival between 91 days and 1 year. Safety outcomes included severe adverse events (SAEs), including symptomatic pulmonary vein (PV) stenosis, atrioesophagal fistula, cardiac tamponade, stroke, thromboembolism events, myocardial infarction, and major bleeding. Results A total of 134 patients were enrolled, of whom 74 underwent PVI using HP-AI, while 60 received low power-AI ablation. After a mean follow-up time of 7.4 months, 22 (16.4%) patients showed arrhythmia recurrence: 5 (6.8%) patients in the HP-AI group and 17 (28.3%) patients in the low power-AI group. The HP-AI group showed a significantly higher arrhythmia-free survival than the low power-AI group (p = 0.011). Two patients in the low power-AI group and 1 patient in the HP-AI group developed an SAE (p = NS). Compared with the low power-AI group, the HP-AI group demonstrated a higher PV first-pass isolation rate, shorter ablation time, and fewer patients with anatomical leakages and sites of unreached AI. Conclusion In a milder AI setting, HP-AI ablation might result in significantly higher arrhythmia-free survival than low power-AI ablation and a similar safety profile.